Can we model the effect of observed sea level rise on tides? - Schindelegger, Michael; Green, Mattias; Wilmes, Sophie-Berenice; Haigh, Ivan (Journal of Geophysical Research: Oceans, 2018)
The link between secular changes in the lunar semidiurnal ocean tide (M2) and relative sea level rise is examined based on numerical tidal modeling and the analysis of long-term sea level records from Europe, Australia, and the North American Atlantic coasts. The study sets itself apart from previous work by using a 1/12° global tide model that incorporates the effects of self-attraction and loading through time-step-wise spherical harmonic transforms instead of iteration. This novel self-attraction and loading implementation incurs moderate computational overheads (some 50%) and facilitates the simulation of shelf sea tides with a global root mean square error of 14.6 cm in depths shallower than 1,000 m. To reproduce measured tidal changes in recent decades, the model is perturbed with realistic water depth changes, compiled from maps of altimetric sea level trends and postglacial crustal rebound. The M2 response to the adopted sea level rise scenarios exhibits peak sensitivities in the North Atlantic and many marginal seas, with relative magnitudes of 1–5% per century. Comparisons with a collection of 45 tide gauge records reveals that the model reproduces the sign of the observed amplitude trends in 80% of the cases and captures considerable fractions of the absolute M2 variability, specifically for stations in the Gulf of Mexico and the Chesapeake-Delaware Bay system. While measured-to-model disparities remain large in several key locations, such as the European Shelf, the study is deemed a major step toward credible predictions of secular changes in the main components of the ocean tide.